The use of personal protection equipment in COVID-19 times: a literature review (Research, Society and Development, 2021)
This study proposes to describe and reflect on the use of personal protective equipment (PPE) by professionals working in the care chain of people with suspected or confirmed contamination by the new Coronavirus. This is integrative review, which analyzed a set of 10 (ten) articles mapped through the Virtual Health Library (VHL). With the conclusion of the study, the results obtained show that it is opportune to approach, according to the literature in question, the topic in the current context of the pandemic of COVID-19, as the mapped studies emphasize, for individuals who experience care about the disease , the urgent understanding of the importance of using PPE, while helping the Nursing area and other health professionals in the proper handling of equipment. Finally, the conclusions highlight the systematic and aggravated picture of illness, death and the precarious performance of this group of professionals, especially today, during the pandemic of COVID-19.